Usaha Ternak Sapi Perah di Kelompok Usaha Bersama (KUB) Tirtasari Kresna Gemilang: Identifikasi Sumber Daya dan Kajian Aspek Kerentanan - Amam, Amam; Jadmiko, Moh. Wildan; Harsita, Pradiptya Ayu; Yulianto, Roni; Widodo, Nur; Soetriono, Soetriono; Poerwoko, Moh. Setyo (Jurnal Ilmu Peternakan dan Veteriner Tropis (Journal of Tropical Animal and Veterinary Science), 2020)
Resources have an important role in livestock farming business, while the aspect of vulnerability can hamper the development of livestock farming business. The purpose of this study is to identify the resources of dairy cattle farming business and examine its effects on the aspects of vulnerability. The resources of this study consisted of economic resources, environmental resources, and social resources. The research was conducted in June-September 2019 at the Joint Business Group (KUB) of Tirtasari Kresna Gemilang which is located in Malang District, East Java Province. The 174 respondents are all dairy farmers who are the members of the group. The data collection methods used are Focus on Group Discussion (FGD), observation, and survey. The survey method was carried out through interviews and questionnaires. Data were analyzed using the Partial Least Square (PLS) method. The results showed that the vulnerability aspect of dairy cattle farming business was positively and significantly affected by economic and environmental resources (0,249 and 0,317, respectively). On the other hand, social resources had a negative influence, although it was not significant to the vulnerability aspect of dairy cattle farming business. The conclusion of the research shows that the aspect of the vulnerability of dairy cattle farming business is influenced by economic, environmental, and social resources by 29.5%.